National Trends in Colorectal Cancer Incidence Among Older and Younger Adults in Canada - Brenner, Darren R. (JAMA Netw Open, 2019)
IMPORTANCE: Recent evidence has shown that although the incidence of colorectal cancer (CRC) is decreasing among older adults, rates have increased in adults younger than 50 years. Given that younger adults are typically classified as at low risk for the disease, this epidemiologic shift is cause for concern. OBJECTIVE: To analyze Canadian national cancer incidence registries to determine incidence trends for CRC among older and younger adults, updated to 2015. DESIGN, SETTING, AND PARTICIPANTS: This cohort study determined the incidence of CRC using data from the National Cancer Incidence Reporting System (1969-1992) and the Canadian Cancer Registry (1992-2015). All Canadians diagnosed with CRC from January 1, 1969, through December 31, 2015, were included in this study. Trends among men and women were examined separately and by age category (>50 vs <50 years). Birth cohort models were fit using 5-year groups starting in 1886, with 1936 as the reference cohort. Data were analyzed from May 13, 2018 to May 16, 2018. MAIN OUTCOMES AND MEASURES: Annualized percentage changes and incidence rate ratios of CRC. RESULTS: From 1971 to 2015, 688 515 incident cases (52.9% women) of CRC were identified. Although the incidence of CRC has decreased in older men and women, rates among younger men and women have increased since 2006 and 2010, respectively. For women younger than 50 years, incidence has increased with a mean annual percentage change of 4.45% since 2010; for men younger than 50 years, a mean annual percentage change of 3.47% from 2006 through 2015. There was an association between CRC incidence and birth cohort, with more recent cohorts being at greater risk than those born earlier. For men, the risk of colorectal cancer in the youngest cohort is more than double that of the reference (incidence rate ratio, 2.57; 95% CI, 1.32-5.02). Incidence rate ratios were not significant for women (IRR, 2.12; 95% CI, 0.95-4.70) but increased in successively younger cohorts. CONCLUSIONS AND RELEVANCE: This study found increasing incidence of colorectal cancer diagnoses among Canadian men and women younger than 50 years of age. This increase in incidence among a low-risk population calls for additional research on possible risk factors that may be affecting these younger cohorts. It appears that primary prevention should be the highest priority to reduce the number of younger adults developing CRC in the future.